Importance of two-dimensional strain imaging in diagnosis of coronary artery disease - Hussein, Ahmed M.; Alzaidi, Mahdi S.; Abed, Bashar M. (Journal of the Faculty of Medicine Baghdad, 2019)
Background: Strain imaging assessing regional myocardial deformation and can be used to quantify regional myocardial function and differentiate between ischemic and non ischemic myocardium. Objectives: to assess sensitivity and specificity of strain imaging in detection of coronary artery disease in comparison with coronary angiography. Patients and Methods: ninety six patients were referred to Ibn albitar center for cardiac surgery, Baghdad, Iraq with symptoms of coronary artery disease for a period between June 2014 and April 2015, all of whom were evaluated by two dimensional echocardiography and all were found to have good left ventricular systolic function with no regional wall motion abnormalities (RWMA), coronary angiography were done for all patients. Results: of the 96 patients: 69(71.9%) were males and 27(28.1%) females, with mean age 55.7 ± 9.71 years. Thirty-one (32.3%) patients have no significant coronary artery disease and sixty-five (67.7%) have significant coronary artery disease. The sensitivity and specificity of global longitudinal strain in detection of coronary artery disease are 67.7% and 80.6% respectively. Global longitudinal strain appears to be useful in localization of coronary artery disease. Conclusions: speckle tracking Strain echocardiography is simple, noninvasive and non-angle dependent with acceptable sensitivity and specificity in early detection of cardiomyopathy including ischemic myopathy.